Evaluation and Design Recommendation of Interactive Mobile Learning Application for Individuals with Intellectual Disabilities - Hardiyanti, Margareta; Thaha, Taufik Kemal; Arifudin, Nanang; Saputra, Muhardi (Journal of Internet and Software Engineering, 2023)
This study evaluates the usability of an app designed to improve literacy skills in individuals with intellectual disabilities named "Baca Yuk". The qualitative field usability studies engaged teachers specializing in working with individuals with disabilities, totaling twelve participants from two special needs schools. Usability issues were categorized into two groups: accessing learning materials and learning practice. These issues included challenges in recognizing speaker button status, forming syllables, pairing letters, dealing with multiple-choice questions, managing small text and touch areas, and comprehending complex image illustrations. From these issues, design recommendations were formulated to enhance the user interface and user experience for individuals with intellectual disabilities. Recommendations emphasized providing clear visual feedback, introducing tutorial screens for unfamiliar actions, simplifying complex processes, enlarging clickable areas and text, prioritizing simplicity in image illustrations, and reducing the number of answer options in multiple-choice questions. Additionally, valuable participant suggestions were considered, such as incorporating audio instructions, avoiding scrolling interfaces, and integrating audio feedback for quizzes. These suggestions aim to enhance accessibility and user-friendliness for individuals with intellectual disabilities which hold practical value for developers and designers striving to create inclusive and effective learning experiences for this unique user group.